A Continuous-Flow, Two-Step, Metal-Free Process for the Synthesis of Differently Substituted Chiral 1,2-Diamino Derivatives - Pirola, Margherita; Compostella, Maria Elena; Raimondi, Laura; Puglisi, Alessandra; Benaglia, Maurizio (Synthesis, 2018)
The enantioselective organocatalytic reduction of aryl-substituted nitroenamines was successfully performed under continuous-flow conditions. After a preliminary screening with a 10-μL microreactor, to establish the best reaction conditions, the reduction was scaled up in a 0.5-mL mesoreactor, without appreciable loss of enantioselectivity, that remained constantly higher than 90%. The in-flow nitro reduction was also accomplished, either by Raney nickel catalyzed hydrogenation or by a metal-free methodology based on the use of the very inexpensive and readily available reducing agent trichlorosilane. The final aim is to develop a two-step, continuous-flow process for the stereoselective, metal-free, catalytic synthesis of differently functionalized chiral 1,2-diamines.
Keywords: flow chemistry; chiral diamines; microreactors; nitroenamines; organocatalysis